N2O emission and bacterial community dynamics during realization of the partial nitrification process. Issue 43 (5th July 2018) - Liu, Xiaolin; Ni, Shou-Qing; Guo, Wenshan; Wang, Zhibin; Ahmad, Hafiz Adeel; Gao, Baoyu; Fang, Xu
Abstract : In this study, greenhouse gas emissions and microbial community succession during the realization of the partial nitrification (PN) process were studied. Abstract : In this study, greenhouse gas emissions and microbial community succession during the realization of the partial nitrification (PN) process were studied. The results show that N2 O emission mainly occurred in the aerobic stage and the PN reactor released about 20 mg of N2 O gas each cycle. There is a positive correlation between the dissolved N2 O concentration and the temperature of a typical cycle. High-throughput sequencing was used to illustrate succession in the microbial community structure. The most significant microfloral change during the PN startup process was that some aerobic bacteria were relatively enriched and some anaerobic bacteria were weeded out. The ammonia oxidizing bacteria (AOB) like Nitrosomonadaceae were enriched on account of the suitable external environment. Pseudomonas whose main function is denitrification declined and Planctomyces (anammox) showed the same tendency. This study comprehensively demonstrates the fluctuations of dissolved and emitted N2 O while researching the succession of the microbial community in the culture of the PN process.